2011
DOI: 10.1142/s0219581x11008228
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Assembled Polyacrylonitrile-Based Carbon Nanofiber Prepared Electrospinning Process

Abstract: Electrospinning is a very simple and versatile process by which polymer nanofibers with diameters ranging from a few nanometers to several micrometers can be produced using an electrostatically driven jet of polymer solution (or polymer melt). Significant progress has been made in this process throughout the last decade and the resultant nanostructures have been exploited to a wide range of applications. An important feature of the electrospinning process is that electrospinning nanofibers are produced in atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…For viscosity, the predicted scaling coefficient is close to the average scaling predicted from the experimental studies. For flow rate however, the average of the three scaling coefficients obtained from experimental studies is 0.325 (Liu et al 2007 ; Mataram et al 2011 ; Wang et al 2008 ), which is lower than 0.5. For △ V , L and K there are very few methodical studies (with experimental data) available in literature to compare the coefficient values.…”
Section: Scaling Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…For viscosity, the predicted scaling coefficient is close to the average scaling predicted from the experimental studies. For flow rate however, the average of the three scaling coefficients obtained from experimental studies is 0.325 (Liu et al 2007 ; Mataram et al 2011 ; Wang et al 2008 ), which is lower than 0.5. For △ V , L and K there are very few methodical studies (with experimental data) available in literature to compare the coefficient values.…”
Section: Scaling Analysismentioning
confidence: 95%
“…While there are many studies which reported that d f increases with increasing flow rate, only few of them have shown systematic data which gives scaling coefficient between the two. Experimental data provided by Wang et al ( 2008 ), Liu et al ( 2007 ) and Mataram et al ( 2011 ) was used to extract the scaling coefficient for Q as 0.3, 0.34 and 0.35 respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamental changes in both chemical composition and physical properties occur during each of these fabrication steps. For instance, stabilization, which occurs in an oxidizing atmosphere at temperatures of 180–300 °C, causes a number of chemical reactions including cyclization, dehydrogenation, aromatization, oxidation, and cross-linking formation among linear polymer chains. These various reactions can result in mechanical weakening of the fiber . During the early stages of carbonization, intermolecular dehydrogenation and cross-linking reactions occur in the oxidized PAN.…”
Section: Introductionmentioning
confidence: 99%
“…The process due to its simplicity has been explored for spinning fibers from a large number of polymers (Mataram, Ismail, Abdullah, Ng, & Matsuura, 2011). In the last decade, significant progress has been made in this process and resultant nanostructures have been exploited for a wide range of applications (Huang, Zhang, Kotaki, & Ramakrishna, 2003).…”
Section: Introductionmentioning
confidence: 99%